Convergent genetic and expression data implicate immunity in Alzheimer's disease. Issue 6 (19th December 2014) - ,; Jones, Lesley; Lambert, Jean‐Charles; Wang, Li‐San; Choi, Seung‐Hoan; Harold, Denise; Vedernikov, Alexey; Escott‐Price, Valentina; Stone, Timothy; Richards, Alexander; Bellenguez, Céline; Ibrahim‐Verbaas, Carla A.; et al.
Abstract: Background: Late‐onset Alzheimer's disease (AD) is heritable with 20 genes showing genome‐wide association in the International Genomics of Alzheimer's Project (IGAP). To identify the biology underlying the disease, we extended these genetic data in a pathway analysis. Methods: The ALIGATOR and GSEA algorithms were used in the IGAP data to identify associated functional pathways and correlated gene expression networks in human brain. Results: ALIGATOR identified an excess of curated biological pathways showing enrichment of association. Enriched areas of biology included the immune response ( P  = 3.27 × 10 −12 after multiple testing correction for pathways), regulation of endocytosis ( P  = 1.31 × 10 −11 ), cholesterol transport ( P  = 2.96 × 10 −9 ), and proteasome‐ubiquitin activity ( P  = 1.34 × 10 −6 ). Correlated gene expression analysis identified four significant network modules, all related to the immune response (corrected P = .002–.05). Conclusions: The immune response, regulation of endocytosis, cholesterol transport, and protein ubiquitination represent prime targets for AD therapeutics.